PERCEPTION AND ROLE OF LECTURERS’ PRACTICAL WISDOM IN THE INITIAL IMPLEMENTATION OF RELIGIOUS MODERATION FOR GENERAL COURSES - Mahpur, Mohammad; Rosdiana, Aprilian Mega; Wafa, Iqbal Ali; Jamilah, Jamilah; Pramitha, Devi (Psikis : Jurnal Psikologi Islami, 2023)
The perception and role of practical wisdom in implementing religious moderation policies which are built from the lecturer's perspective are open and democratic because they uphold academic culture. However, the unsystematic implementation of top-down policies has the potential to ignore the creative participation of task implementers in the field. The approach to insert religious moderation is stronger when listening to the good practices of learning implementers, namely lecturers. This article aimed to find out the role of lecturers' initiatives in strengthening religious moderation as implementers of learning in non-religious courses. The research was conducted with a qualitative phenomenological type. The research participants involved twenty-seven non-religious lecturers from 9 study programs. The data were extracted using the technique of focused group discussions and document analysis. The results of the lecturers’ practical wisdom are as follows, 1) religious moderation is perceived by lecturers as a wise view in responding to differences, a middle-way view that is not extreme to the left and right, and the ability to moderate multiculturally; 2) lecturers as learning actors in the field have creative, authentic and autonomous goodwill in inserting religious moderation so that responsive lecturers are found to prevent early risks of student radicalism, intolerance, and religious exclusivism; 3) lecturers can find learning methods in class by inserting religious moderation in general courses even though there are no technical-operational instructions in the learning process. It showed that lecturers in the context of implementing religious moderation responded quickly so that their practical wisdom provides solutions to accelerate the achievement of religious moderation that is actually more participatory.